Shared HLA class II in six autoimmune diseases in Latin America: A meta-analysis. (2012)
The prevalence and genetic susceptibility of autoimmune diseases (ADs) may vary depending on latitudinal gradient and ethnicity. The aims of this study were to identify common human leukocyte antigen (HLA) class II alleles that contribute to susceptibility to six ADs in Latin Americans through a meta-analysis and to review additional clinical, immunological, and genetic characteristics of those ADs sharing HLA alleles. DRB1()03:01 (OR: 4.04; 95%CI: 1.41-11.53) was found to be a risk factor for systemic lupus erythematosus (SLE), Sjogren's syndrome (SS), and type 1 diabetes mellitus (T1D). DRB1()04:05 (OR: 4.64; 95%CI: 2.14-10.05) influences autoimmune hepatitis (AIH), rheumatoid arthritis (RA), and T1D; DRB1()04:01 (OR: 3.86; 95%CI: 2.32-6.42) is a susceptibility factor for RA and T1D. Opposite associations were found between multiple sclerosis (MS) and T1D. DQB1()06:02 and DRB1()15 alleles were risk factors for MS but protective factors for T1D. Likewise, DQB1()06:03 allele was a risk factor for AIH but a protective one for T1D. Several common autoantibodies and clinical associations as well as additional shared genes have been reported in these ADs, which are reviewed herein. These results indicate that in Latin Americans ADs share major loci and immune characteristics.